Preventive Measures and Their Effects on Human Health to Fight Against SARS-Covid-19. - Muhammad Akif1 , Hira Hira2 , Muhammad Ahsan3 , Shaukat Abbas4 , Sonia Rafique5 , Muhammad Asif 1* (AlQalam Journal of Medical and Applied Sciences, 2020)
SARS Covid-19 is a pandemic, highjack the economy of the world, spread fear among the people, although it was not so serious as it was taken and as it was explained by media and analyst. This wrong explanation leads the people towards highly sophisticated preventive measure to remain safe from the effect of Covid-19. But due to excessive stress of media the people exaggerated in taking preventive measures, which also started to show their negative impact, like constant use of mask can cause respiratory problems particularly during working and exercise, excessive washing of hand can weakens the immune system, social distancing also causes stress which eventually leads to weakens our immunity, excessive use of vitamin D resources, Organic diets are also not good for health, a balance life is only a key for a good immunity and good health, Preventive measures are necessary but their improper and excessive use can also affect the immune system very badly, which leads to easy attack of Covid-19 or any other disease. This review showed the importance of preventive measures, their proper use and negative impact of improper uses.